Total joint replacement may be a valuable treatment for Aboriginal and Torres Strait Islander people with osteoarthritis, but uptake is low. Issue 10 (13th August 2022) - O'Brien, Penny; Thuraisingam, Sharmala; Bunzli, Samantha; Lin, Ivan; Bessarab, Dawn; Coffin, Juli; Choong, Peter F. M.; Dowsey, Michelle M.
Abstract: Background: Despite bearing a higher burden of osteoarthritis, little research has examined disparities in the access, utilisation and surgical outcomes associated with total joint replacement (TJR) among Aboriginal and Torres Strait Islander people. Methods: We conducted a retrospective cohort study to compare the sociodemographic and clinical characteristics of all Aboriginal and Torres Strait Islander and non‐Aboriginal patients who underwent primary hip and knee replacement at St Vincent's Hospital Melbourne between 1996 and 2019. Results: A total of 10 277 primary total knee or hip replacements were performed in the 1996–2019 study period, of which 49 (0.5%) patients identified as either Aboriginal and/or Torres Strait Islander. Aboriginal and Torres Strait Islander patients were younger (61.7 ± 11.8 vs. 68.3 ± 10.3 years; P < 0.001), recorded higher Body Mass Index scores (median (IQR), 36.0 (29.5–41.4) vs. 30.8 (27.0–35.3); P < 0.001) and were more likely to experience multiple co‐morbidities at the time of surgery. Despite these findings, Aboriginal and Torres Strait Islander patients did not experience higher complication rates and experienced comparable, clinically meaningful quality of life improvements 12‐months post‐surgery. Conclusions: TJR appears to be a valuable treatment option for Aboriginal and Torres Strait Islander people with end‐stage osteoarthritis. Our study was limited by the small number of procedures conducted in patients who identify as Aboriginal and Torres Strait Islander. Further research is needed to understand why uptake of TJR by Aboriginal and Torres Strait Islander people is low. Abstract : Despite bearing a higher burden of osteoarthritis, little research has examined disparities in the access, utilisation and surgical outcomes associated with total joint replacement (TJR) in Aboriginal and Torres Strait Islander people. We conducted a retrospective cohort study to compare the sociodemographic and clinical characteristics of all Aboriginal and Torres Strait Islander and non‐Aboriginal patients who underwent primary hip and knee replacement at St Vincent's Hospital Melbourne between 1996 and 2019. A total of 10, 277 primary total knee or hip replacements were performed in the 23‐year study period, of which 49 (0.5%) patients identified as either Aboriginal and/or Torres Strait Islander. Further investigation is needed to better understand the factors influencing low access and uptake of TJR in Aboriginal and Torres Strait Islander people.